Ending poverty is urgent: Determining the factors that affect prosocial crowdfunding success - Paz, Francisca Lisboa (2022)
Extreme poverty is a problem that affects around 9% of the world's population and credit is almost inaccessible to the most disadvantaged populations. To fight poverty and reduce financial exclusion, several approaches have been used, with microcredit being one of them. As technology advances, prosocial crowdfunding has come to play as an alternative to traditional microcredit. This study aimed to identify some factors that might contribute to reducing prosocial crowdfunding campaigns’ duration, to help disadvantaged people to access credit in a faster way, contributing to poverty reduction, and how do those factors behave in a recession year. We applied two multiple linear regressions: regression 1 covered campaigns published in the years 2017-2020 (N=791534) and regression 2 covered campaigns published exclusively in the year 2020 (N=171498). Based on regression 1, we concluded that campaigns with longer loan terms, with a higher number of hashtags, with monthly repayment terms, individual, and related to the agriculture sector, are associated with slower campaigns and that campaigns with longer descriptions, with borrowers from higher HDIs countries, with English as the original language and whose borrowers are women, are associated with faster campaigns. On the other hand, based on regression 2, we concluded that the only two factors associated with faster campaigns are longer descriptions and female borrowers. However, the loan term is no longer statistically significant in regression 2.